"If it flies, it dies": Profit, workplace pressure and Bird of Prey persecution. (August 2021) - Burnside, Ellen; Pamment, Nick; Collins, Alan
Abstract: Persecution has continued to negatively impact the density and range of many Bird of Prey (raptor) species, both nationally and internationally, despite existing legal protection. Departing from the relatively small body of statistical analyses indicating elevated raptor mortality in proximity to shooting estates, this qualitative study draws on in-depth interviews with retired (hence, free from employment pressure) gamekeepers. New insights and findings are unfolded into the nature and extent of employment-related pressures (from employers) to commit raptor persecution. The findings offer a new narrative in the discourse on the problem, revealing that economic, community and lifestyle pressures co-exist within the gamekeeping industry. It is argued that regulatory design and enforcement strategy and tactics should be mindful of these pressures in order to reduce raptor persecution in both individual criminal liability and vicarious liability settings. Highlights: Persecution negatively impacts the range and density of UK raptor species. Retired gamekeepers were interviewed to solicit insights for the study. Employment -related pressure induces raptor persecution. Regulatory design and enforcement should be mindful of such pressures.